Impairment of Long-term Potentiation and Associative Memory in Mice That Overexpress Extracellular Superoxide Dismutase - Thiels, Edda (J Neurosci, 2000)
Reactive oxygen species, including superoxide, generally are considered neurotoxic molecules whose effects can be alleviated by antioxidants. Different from this view, we show that scavenging of superoxide with an antioxidant enzyme is associated with deficits in hippocampal long-term potentiation (LTP), a putative neural substrate of memory, and hippocampal-mediated memory function. Using transgenic mice that overexpress extracellular superoxide dismutase (EC-SOD), a superoxide scavenger, we found that LTP was impaired in hippocampal area CA1 despite normal LTP in area CA3. The LTP impairment in area CA1 could be reversed by inhibition of EC-SOD. In addition, we found that EC-SOD transgenic mice exhibited impaired long-term memory of fear conditioning to contextual cues despite exhibiting normal short-term memory of the conditioning experience. These findings strongly suggest that superoxide, rather than being considered exclusively a neurotoxic molecule, should also be considered a signaling molecule necessary for normal neuronal function.